DNA methyltransferase 1 mutations and mitochondrial pathology: is mtDNA methylated? - Maresca, Alessandra; Zaffagnini, Mirko; Caporali, Leonardo; Carelli, Valerio; Zanna, Claudia (Frontiers in Genetics, 2015)
Autosomal dominant cerebellar ataxia, deafness and narcolepsy (ADCA-DN) and Hereditary sensory neuropathy with dementia and hearing loss (HSN1E) are two rare, overlapping neurodegenerative syndromes that have been recently linked to allelic dominant pathogenic mutations in the DNMT1 gene, coding for DNA (cytosine-5)-methyltransferase 1. DNMT1 is the enzyme responsible for maintaining the nuclear genome methylation patterns during the DNA replication and repair, thus regulating gene expression. The mutations responsible for ADCA-DN and HSN1E affect the replication foci targeting sequence domain, which regulates DNMT1 binding to chromatin. DNMT1 dysfunction is anticipated to lead to a global alteration of the DNA methylation pattern with predictable downstream consequences on gene expression. Interestingly, ADCA-DN and HSN1E phenotypes share some clinical features typical of mitochondrial diseases, such as optic atrophy, peripheral neuropathy and deafness, and some biochemical evidence of mitochondrial dysfunction. The recent discovery of a mitochondrial isoform of DNMT1 and its proposed role in methylating mitochondrial DNA (mtDNA) suggests that DNMT1 mutations may directly affect mtDNA and mitochondrial physiology. On the basis of this latter finding the link between DNMT1 abnormal activity and mitochondrial dysfunction in ADCA-DN and HSN1E appears intuitive, however mtDNA methylation remains highly debated. In the last years several groups demonstrated the presence of 5-methylcytosine in mtDNA by different approaches, but, on the other end, the opposite evidence that mtDNA is not methylated has also been published. Since over 1500 mitochondrial proteins are encoded by the nuclear genome, the altered methylation of these genes may well have a critical role in leading to the mitochondrial impairment observed in ADCA-DN and HSN1E. Thus, many open questions still remain unanswered, such as why mtDNA should be methylated, and how this process is regulated and executed?